Damping and Compressive Properties of SLM-Fabricated Rhombic Dodecahedron-Structured Ni–Ti Shape Memory Alloy Foams - Di Guo; Qingzhou Wang; Li Liu; Shuo Liu; Hao Cao; Jingxia Xie; Fuxing Yin (Metals)
Ni–Ti shape memory alloy (SMA) foams, capable of bringing revolutionary changes to crucial fields such as aerospace, energy engineering, and biomedical applications, are at the forefront of materials science research. With the aim of designing Ni–Ti SMA foams with complex structures, near-equiatomic Ni–Ti SMA foams featuring a rhombic dodecahedron (RD) structure were fabricated using selective laser melting (SLM) technology. Damping, superelasticity, and quasi-static compressive mechanical tests were carried out on the resultant foams. The findings indicated that the smaller the unit structure of the RD or the larger the rod diameter, the higher the damping and compressive strength of the foams would be. Foams with a cell structure of 2 mm × 2 mm × 2 mm and a rod diameter of 0.6 mm exhibited the highest damping, reaching up to 0.049, along with the highest compressive strength, reaching up to 145 MPa. Furthermore, if the specimen underwent solution and aging heat treatments, its strength could be further enhanced. Meanwhile, the specimens also exhibited excellent superelasticity; even when the pre-strain was 6%, the elastic recovery could still reach 97%. Based on microstructure characterization and finite element simulation, the property mechanisms and deformation rules of the foams were revealed.